LEGAL PROTECTION OF AVIATION IN THE CONTEXT OF GLOBALIZATION, RISKS AND SOCIAL ENTROPY AS A SCIENTIFIC PROBLEM: APPROACHES AND SOLUTIONS - O. O. Chernaya (Научный вестник МГТУ ГА, 2016)
The article considers the issue concerning the international legal problem of using armed forces to counter the threats posed by the misuse of civil aircraft, in particular, the use of civil aircraft as a weapon to kill people and destroy objects on the territory of States (the events of 11th September 2001 in the USA). It proves the need for universal international legal norms regulating the actions of States to prevent and suppress acts of the misuse of civil aircraft.